Design of active NiCo2O4-Δ spinel catalyst for abatement of CO-CH4 emissions from CNG fueled vehicles - Trivedi S.; Prasad R.; Gautam S.K. (My University, 2025)
Increasing number of CNG vehicles on road emits considerable amount of CO, a poisonous gas and CH4, a greenhouse-gas. Highly active and oxygen-deficient NiCo2O4-δ spinel and its individual metal-oxides were synthesized by calcination of precipitated/co-precipitated basic-carbonates followed by calcination under different strategies of stagnant air(s), flowing air(f) and reactive calcination(RC) for total oxidation of CO-CH4 mixture. The catalysts were characterized by XRD, XPS, BET surface-area, SEM-EDX and TEM. The performance order of the catalysts for the oxidation of CO-CH4 mixture was as follows: NiCoRC>NiCof>NiCos>CoRC>Cof>Cos>NiRC> Nif>Nis. The pairing of Ni and Co in spinel-structure together with RC produced catalyst was oxygen-deficient highly active for total oxidation of the mixture at the lowest temperature of 350°C. The NiCoRC was found stable under reaction-conditions for 50h at 350°C and after four successive heating (350°C)-cooling (35°C) cycles besides accelerated-aging tests up to 600°C. © 2018 American Institute of Chemical Engineers AIChE J, 64: 2632–2646, 2018. © 2018 American Institute of Chemical Engineers